FUNGSI INFORMASI BUTIR PADA RAGAM BENTUK SOAL PILIHAN GANDA - NOVI INDAH EARLYANTI (PROGRAM STUDI PENELITIAN DAN EVALUASI PENDIDIKAN, 2012)
The objective of the research was to compare item information function logistic model of two parameter by viewing forms of multiple choice test and scoring model. Independent variable of this research are correct score (CS) and punishment score (PS). And also Ordinary Multiple Choice Items (PGB) and Association of Multiple Choice Items (PGA). To see this comparison, the item information function are compared by ÂµImax. For the student corrected by CS model compared between the group who answer Ordinary Multiple Choice Items and Association of Multiple Choice Items. For the student corrected by PS model compared between the group who answer Ordinary Multiple Choice Items and Association of Multiple Choice Items. While for the group of student doing test with Ordinary Multiple Choice Items compared beetwen the couple CS and PS and for the group of student doing test with Association of Multiple Choice Items compared beewen the couple CS and PS. The result of this research inidicate that, first, for students who were given about the form of PGA, students' answers are corrected with PS produced an average maximum value of the items information function is higher with students who corrected with CS. Second, for students who were given about the form of PGB, students are given a warning (PS) produced a mean maximum value of the item information function is higher than the average maximum value of the function item information of students who were not given warning (CS). Third, to answer students were given a warning (PS), students were given about the form of PGA produced a mean maximum value of information function item higher than students who were given about the form of PGB. Fourth, to answer the students who were not given warning (CS), students were given about the form of PGA produced a mean maximum value of information function items higher than students who were given about the form of PGB.